Comparison of Corrosion Behavior of Electrochemically Deposited Nano-Cobalt-Coated Ni Sheet - Nasser Al-Aqeeli; Ihsan-ul-Haq Toor (Journal of Chemistry)
Corrosion behavior of nano-coblat-coated Ni sheet was compared with pure Ni and 20% Fe-Ni alloy sheet using potentiodynamic polarization and linear polarization technique in 0.1 M NaCl solution at room temperature. Results showed that corrosion resistance properties of nano-Co-coated Ni sheet were almost same as that of pure Ni sheet, however corrosion resistance of 20% Fe-Ni sheet was decreased significantly. Pitting potential of 20% Fe-Ni sheet was subsequently decreased as compared to pure Ni sheet as well as nano-cobalt-coated Ni sheet. SEM/EDS analysis of the corroded surfaces showed that both pure Ni and nano-coblat-coated Ni sheet did not show any appreciable corrosion however significant corrosion was observed in the case of 20% Fe-Ni sheet.